2016
DOI: 10.1097/qai.0000000000000838
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of Frequent HIV Testing of High-Risk Populations in the United States

Abstract: Supplemental Digital Content is Available in the Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 37 publications
2
48
0
5
Order By: Relevance
“…[14,15,26] In the USA, where MSM are more aware of their HIV serostatus than in Peru, testing is more frequent and frequent testing has been shown to be cost-effective. [24,27] Additionally, consistent with the literature, our study found higher educational attainment was associated with participants knowing their HIV-infection status. [11,28] This suggests that strategies that encourage and facilitate frequent HIV testing among MSM and transgender women, particularly those with lower educational attainment, could be beneficial.…”
Section: Discussionsupporting
confidence: 89%
“…[14,15,26] In the USA, where MSM are more aware of their HIV serostatus than in Peru, testing is more frequent and frequent testing has been shown to be cost-effective. [24,27] Additionally, consistent with the literature, our study found higher educational attainment was associated with participants knowing their HIV-infection status. [11,28] This suggests that strategies that encourage and facilitate frequent HIV testing among MSM and transgender women, particularly those with lower educational attainment, could be beneficial.…”
Section: Discussionsupporting
confidence: 89%
“…This may be reflected in previously reported increases in HIV diagnoses among young MSM who are most likely to have undiagnosed HIV, and the overall increase in awareness of HIV infection among MSM [4,11]. Annual testing is recommended for sexually active MSM and more frequent testing may be indicated for those at highest risk for HIV infection to detect HIV infection early, which allows risk counseling and initiation of treatment and is cost effective [32-34]. Additional assessments are needed to determine whether testing is not reaching certain subpopulations of MSM at high risk for HIV infection.…”
Section: Discussionmentioning
confidence: 99%
“…In high-income countries such as the United Kingdom, annual targeted testing to MSM, IDUs, and people from HIV-endemic countries has been reported to prevent 4%-15% of infections and require testing 2,500 people per HIV diagnosis, with an ICER of £17,500/QALY gained (~$26,700, 2012 USD) [23]. Testing MSM more frequently (at 3 or 6 month intervals) is reported to be cost-effective and even cost-saving in some scenarios over a one-year period in the United States [24]. A study based in Zimbabwe quantified the potential savings in health care costs with HIV self-testing: while only 7,000 DALYs are averted over 20 years in a population of 7.5 million, the authors suggest the $75 million saved by self-testing might be used to avert further DALYs by investing this money in other highly cost-effective prevention or treatment interventions [25].…”
Section: Hiv Prevention Interventionsmentioning
confidence: 99%